'DAVID'S STORY—BORN TO FAIL THE PERFECT STORM'. (7th October 2012) - Carnochan, J
Abstract : Violence, in all its forms, infects the well being and health of communities throughout the World, the daily stress and fear experienced by individuals and families inhibits lives and aspirations. Violence is preventable, but criminal justice solutions alone cannot achieve this. Violence is situated within a complicated and complex landscape of causes, societal conditions, personal circumstances, individual characteristics, attitudes and cultures. The principal of prevention is gaining increasing currency and the application of a public health model provides a framework of understanding, a clear identification of the components of violence, a means to articulate solutions to a complex multi sectoral problem and a methodology founded in a robust science based process of evaluation. Different agencies are already dealing directly with the same people as victims, offenders, patients, clients, students and tenants; already we can identify the shared agenda. The effective coordination of services that are appropriate, proportionate and timely and focussed on positive outcomes is the most viable response. Primary prevention must be at the heart of all our collaborative efforts. Preventing violence through the development of safe, stable and nurturing relationships between children and their caregivers must become a key component of national strategy. 'David's Story' is a factual narrative of the life of a young man convicted of culpable homicide when he was 15. The story will highlight some of the circumstances and social conditions that increased his vulnerability and at the same time identify those opportunities where effective intervention may have changed his life course.